Exploring the barriers and enablers of industrial solutions in renovation projects: a mixed-methods study in the finnish AEC industry - Chauhan, Krishna; Peltokorpi, Antti; Lavikka, Rita; Seppänen, Olli (Frontiers in Built Environment, 2024)
Offsite construction is a major approach to promote industrialisation in construction. However, implementation of prevailing industrial solutions is often less adequate and unsatisfactory, especially in renovation projects. Thus, the overall objective of this study is to understand the reasons behind the poor performance in implementation of the industrial solutions. The specific objectives include identifying the prominent barriers and enablers of prefabricated products in renovation projects. This study employed exploratory sequential mixed method. The qualitative data were gathered via semi-structured interviews to collect experiences and perception of experts related to industrial solutions. This was followed by quantitative data collection via questionnaire survey using a seven-point Likert scale. The major barriers and enablers of industrial solutions in renovation projects have been ranked in this study. The findings reveal that immutability of heritage buildings, the tolerances of old buildings and insufficient spaces to ensure construction work ranked the top three barriers for implementing industrial solutions in renovation projects. Moreover, the study identifies the most significant enablers including shorter project schedules, quality improvement and work safety improvement. The novelty of the research lies in the comprehensive presentation of the barriers and enablers of industrial solutions in the renovation project context. Policymakers, designers, and contractors can utilize these findings as guiding principles to enhance decision-making processes and create viable solutions for the obstacles encountered in renovation projects. This study further represents a vital step towards the efficient and effective implementation of industrial solutions in renovation projects, resulting in more sustainable and cost-effective outcomes.